Knockdown of DEC2 expression inhibits the proliferation of mesangial cells through suppressed glycolysis and p38 MAPK/Erk pathway in lupus nephritis - Huimeng Qi; Li Xu; Qiang Liu (BMC, 2023)
Abstract Background To elucidate the mechanism by which DEC2 modulates the proliferation of mesangial cells (MCs) in lupus nephritis (LN). Methods The 32-week-old female Fcgr2b−/− mice and their serum-treated MCs were used as in vivo and in vitro LN model. MCs knocked down of DEC2 and overexpressed with DEC2 were also established. The expression of DEC2 was measured in the kidneys of Fcgr2b−/− mice and LN serum-treated MCs using RT-qPCR and Western blot. MCs proliferation was detected by 5-ethynyl-2'-deoxyuridine (EdU) labeling assay and PCNA expression using immunofluorescence. The glucose metabolism was evaluated in LN serum-treated MCs, and the levels of lactate production, glucose consumption, ATP production and mitochondrial membrane potential were assayed. The glycolysis and mitochondrial respiration function of the MCs were measured using the Extracellular Flux Analyzer. The extracellular acidification rate (ECAR) and oxygen consumption rate (OCR) were dynamically monitored and multiple important bioenergetic parameters can be calculated. The expression of Toll like receptor 4 (TLR4) and glucose transporter 1 (GLUT1) were detected in the MCs. Multiple signaling proteins were screened. Results DEC2 was found overexpressed in the kidney of Fcgr2b−/− LN mice. Knockdown of DEC2 inhibited LN serum-induced MCs proliferation. DEC2 was associated with the glucose metabolism in LN serum-treated MCs. DEC2 regulated glycolysis in LN serum-treated MCs. DEC2 was associated with mitochondrial fitness in LN serum treated MCs. DEC2 activated MCs glycolysis through TLR4 and glucose transporter 1 (GLUT1) regulation. DEC2 regulated MCs proliferation through two signaling pathways including dependent and independent of glycolysis, which located in the downstream of TLR4 signaling. Conclusion Knockdown of DEC2 expression inhibits the proliferation of MCs through suppressed glycolysis and p38 MAPK/ERK pathway in LN.